Flame-retardant electrode and all-solid-state battery comprising same

By inserting a flame retardant layer with a core-shell structure between the electrode current collector of the lithium secondary battery and the active material layer, the problem of thermal runaway of the lithium secondary battery is solved, the thermal stability and adhesion of the battery are improved, and the safety and performance of the battery are ensured.

CN119673953APending Publication Date: 2025-03-21HYUNDAI MOTOR CO LTD +1
View PDF 0 Cites 0 Cited by

Patent Information

Application Number
CN202410403112.5
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Priority Date
2023-09-21
Filing Date
2024-04-03
Publication Date
2025-03-21

AI Technical Summary

Technical Problem

Lithium secondary batteries are prone to internal short circuits during repeated charging and discharging, resulting in thermal runaway, and thermal runaway may also occur during external impact or deformation, affecting the safety of electric vehicles.

Method used

A flame retardant layer is inserted between the electrode current collector and the electrode active material layer, which includes a flame retardant having a core-shell structure, an adhesive and a first conductive material, and the surface of the flame retardant material is coated through the conductive material to improve electronic conductivity and adhesion.

Benefits of technology

Improves the thermal stability and adhesion of the electrodes, reduces the risk of thermal runaway, and ensures the safety and electrochemical performance of the battery.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119673953A_ABST
    Figure CN119673953A_ABST
Patent Text Reader

Abstract

The invention provides a flame-retardant electrode and an all-solid-state battery including the flame-retardant electrode. Embodiments of the flame-retardant electrode include a flame-retardant layer between an electrode current collector and an electrode active material layer, and embodiments of an all-solid-state battery including the flame-retardant electrode, in which the flame-retardant layer includes a flame retardant configured such that a surface of the flame-retardant material is coated with a conductive material, thereby increasing thermal stability and adhesion to the electrode current collector.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present disclosure relates to flame retardant electrodes for all-solid-state batteries. Background Art

[0002] Recently, in order to solve the problem of carbon dioxide (CO 2 ) has avoided the use of fossil fuels due to environmental problems caused by electric vehicles using secondary batteries, and thus the automobile (as a means of transportation) industry has shown great interest in electric vehicles using secondary batteries.

[0003] Secondary batteries use materials capable of electrochemical reactions at positive and negative electrodes to store electricity. A representative example of these secondary batteries is a lithium secondary battery that stores electrical energy through a chemical potential difference when lithium ions are intercalated / released at the positive and negative electrodes.

[0004] The lithium secondary battery is manufactured in such a manner that a material capable of reversibly intercalating / deintercalating lithium ions is used as positive and negative electrode active materials, and an organic electrolyte, a polymer electrolyte, or a solid electrolyte is also supported between the positive and negative electrodes.

[0005] When currently developed lithium secondary batteries are used in electric vehicles, they can travel about 400 km on a single charge, but problems such as instability, fire, etc. still occur. Specifically, repeated charging and discharging of the secondary battery may cause internal short circuits between interfaces of various components included in the secondary battery, which may increase internal resistance and cause thermal runaway. In addition, thermal runaway may occur even when the secondary battery is damaged due to external impact or external deformation.

[0006] When a secondary battery is used in a transportation device such as an electric vehicle, thermal runaway of the secondary battery is directly related to human life, and thus thermal stability of the secondary battery emerges as a very important factor. Summary of the invention

[0007] The present disclosure relates to a flame-retardant electrode and an all-solid-state battery including the flame-retardant electrode, wherein the flame-retardant electrode includes a flame-retardant layer disposed between an electrode current collector and an electrode active material layer, wherein the flame-retardant layer may include a flame retardant configured such that a surface of the flame-retardant material is coated with a conductive material, thereby increasing thermal stability and adhesion to the electrode current collector.

[0008] In view of the problems encountered in the prior art, embodiments of the present disclosure have been made, and by inserting a flame retardant layer between the electrode current collector and the electrode active material layer, embodiments of the present disclosure can provide an electrode with improved thermal stability and an all-solid-state battery including the electrode.

[0009] Furthermore, embodiments of the present disclosure provide an electrode having increased adhesive force by interposing a flame retardant layer between an electrode current collector and an electrode active material layer.

[0010] The embodiments of the present disclosure are not necessarily limited to the aforementioned embodiments. The embodiments of the present disclosure can be clearly understood through the following description, and the embodiments of the present disclosure can be implemented through embodiments corresponding to the claims and combinations thereof.

[0011] In an embodiment of the present disclosure, a flame retardant electrode includes an electrode current collector, an electrode active material layer, and a flame retardant layer located between the electrode current collector and the electrode active material layer, wherein the flame retardant layer includes a flame retardant having a core-shell structure, a binder and a first conductive material, and the flame retardant includes a core comprising a flame retardant material and a shell comprising a second conductive material applied to at least a portion of the surface of the core.

[0012] In one embodiment, the thickness of the flame retardant layer may be 10 μm or less.

[0013] In one embodiment, the thickness (w) of the shell may be 2 μm or less.

[0014] In one embodiment, the average particle size (d 50 ) can be 3μm to 5μm.

[0015] In one embodiment, a volume ratio of the core to the sum of the first conductive material and the second conductive material may be 1:1 to 1:100.

[0016] In one embodiment, the flame retardant material may include an inorganic flame retardant material, a phosphorus (P)-based flame retardant material, a halogen-based flame retardant material, a nitrogen (N)-based flame retardant material, and any combination thereof.

[0017] In one embodiment, the inorganic flame retardant material may include aluminum hydroxide (Al(OH) 3 )、Magnesium hydroxide (Mg(OH) 2 ), antimony trioxide (Sb 2 O 3 ), tin hydroxide (Sn(OH) 2 ), tin oxide (SnO), molybdenum trioxide (MoO 3 ), zirconium compounds, calcium salts, boron compounds and any combination thereof.

[0018] In one embodiment, the phosphorus (P)-based flame retardant material may include a red phosphorus (RP)-based flame retardant material, a phosphate-based flame retardant material, a phosphite-based flame retardant material, a phosphite-based flame retardant material, a phosphonate-based flame retardant material, a phosphinate-based flame retardant material, a phosphinate-based flame retardant material, a phosphate-based flame retardant material, a phosphoric acid ester and salt flame-retardant material, and any combination thereof.

[0019] In one embodiment, the halogen-based flame retardant material may include polybrominated diphenyl ether (PBDE), polybrominated biphenyl (PBB), brominated cyclic hydrocarbons, decabromodiphenyl ether (DeBDE), hexabromocyclododecane (HBCDD), tetrabromobisphenol A (TBBP-A), octabromodiphenyl ether (OBDPE), brominated polystyrene, propylene dibromostyrene, brominated epoxy resin, brominated polycarbonate, chlorinated paraffin, chlorinated polyethylene, chlorinated alicyclics, and any combination thereof.

[0020] In one embodiment, the nitrogen (N)-based flame retardant material may include melamine polyphosphate (MPP), melamine cyanurate, melamine, melamine isocyanurate, a triazine-based compound, and any combination thereof.

[0021] In one embodiment, the adhesion of the flame retardant layer to the electrode current collector may be 1.20 gf / mm or greater.

[0022] In one embodiment, the flame retardant layer may include 0.5 wt % to 5 wt % of the binder.

[0023] In one embodiment, the first conductive material and the second conductive material may include a carbon-based conductive material.

[0024] In one embodiment of the present disclosure, an all-solid-state battery includes: a positive electrode including a flame-retardant electrode; a solid electrolyte layer located on the positive electrode and including a solid electrolyte; a negative electrode active material layer located on the solid electrolyte layer; and a negative electrode current collector located on the negative electrode active material layer.

[0025] In an embodiment of the present disclosure, the all-solid-state battery includes: a negative electrode including a flame-retardant electrode, a solid electrolyte layer located on the negative electrode and including a solid electrolyte, a positive electrode active material layer located on the solid electrolyte layer, and a positive electrode current collector located on the positive electrode active material layer. BRIEF DESCRIPTION OF THE DRAWINGS

[0026] The above and other features of the present disclosure will now be described in detail with reference to certain exemplary embodiments of the present disclosure shown in the accompanying drawings, which are given hereinafter by way of illustration only and thus are not limiting of the present disclosure, and in which:

[0027] Figure 1 An electrode according to an embodiment of the present disclosure is exemplarily shown;

[0028] Figure 2 exemplarily illustrates a core-shell structure of a flame retardant according to an embodiment of the present disclosure;

[0029] Figure 3 A lithium secondary battery in which an electrode according to an embodiment of the present disclosure is applied as a positive electrode is exemplarily shown;

[0030] Figure 4 A photograph showing an accelerating calorimeter (ARC) for measuring the thermal stability of an all-solid-state battery according to an embodiment of the present disclosure;

[0031] Figure 5 The results of analyzing the all-solid-state battery according to the embodiment using an accelerating rate calorimeter are shown;

[0032] Figure 6 shows the results of analyzing the secondary battery according to Comparative Example 1 using an accelerating rate calorimeter;

[0033] Figure 7 shows the results of analyzing the all-solid-state batteries according to the examples and the comparative examples using differential scanning calorimetry (DSC); and

[0034] Figure 8 The charge / discharge characteristic results of the all-solid-state batteries according to the embodiment, comparative example 1, and comparative example 3 are shown. DETAILED DESCRIPTION

[0035] The above and other features and advantages of the present disclosure can be more clearly understood from the following embodiments in conjunction with the accompanying drawings. However, the present disclosure is not necessarily limited to the embodiments disclosed herein and can be modified into different forms. These embodiments are provided to thoroughly explain the present disclosure and fully convey information showing the spirit of the present disclosure to those skilled in the art.

[0036] Throughout the accompanying drawings, the same reference numerals can represent the same or similar elements. For the sake of clarity of the present disclosure, the size of the structure may be depicted as being larger than its actual size. It is understood that, although various elements may be described using terms such as "first", "second", etc., in this article, these elements are not necessarily limited by these terms. These terms are only used to distinguish one element from another. For example, without having to depart from the scope of the present disclosure, the "first" element discussed below may be referred to as the "second" element. Similarly, the "second" element may also be referred to as the "first" element. Unless the context clearly indicates otherwise, the singular form as used herein may also include the plural form.

[0037] It is further understood that when used in this specification, the terms "comprises", "includes", "having", etc. specify the presence of stated features, integers, steps, operations, elements, components, or combinations thereof, and do not exclude the presence or addition of one or more other features, integers, steps, operations, elements, components, or combinations thereof. Moreover, it is understood that when an element such as a layer, film, region, or sheet is referred to as being "on" another element, it may be directly on the other element, or there may be intermediate elements therebetween. Similarly, when an element such as a layer, film, region, or sheet is referred to as being "under" another element, it may be directly under the other element, or there may be intermediate elements therebetween.

[0038] Unless otherwise specified, all numerical values, values, and / or representations used in this article to represent the amount of components, reaction conditions, polymer compositions, and mixtures may be considered approximate values, including various uncertainties that affect measurement that occur inherently when obtaining these values, and therefore may be understood in all cases to be modified by the term "about". In addition, when a numerical range is disclosed in this specification, the range may be continuous and may include all values ​​from the minimum value of the range to its maximum value, unless otherwise specified. In addition, when such a range involves integer values, all integers including the minimum value to the maximum value may be included unless otherwise specified.

[0039] In this specification, when a range is described for a variable, it is understood that the variable can include all values, including the endpoints described in the stated range. For example, a range of "5 to 10" can be understood to include any sub-ranges, such as 6 to 10, 7 to 10, 6 to 9, 7 to 9, etc., as well as individual values ​​of 5, 6, 7, 8, 9 and 10, and can also be understood to include any value between the valid integers in the stated range, such as 5.5, 6.5, 7.5, 5.5 to 8.5, 6.5 to 9, etc. In addition, for example, a range of "10% to 30%" can be understood to include sub-ranges, such as 10% to 15%, 12% to 18%, 20% to 30%, etc., and all integers including 10%, 11%, 12%, 13%, etc. up to 30%, and can also be understood to include any value between the valid integers in the stated range, such as 10.5%, 15.5%, 25.5%, etc.

[0040] Figure 1 The flame retardant electrode according to the embodiment of the present disclosure is exemplarily shown. Figure 1 The flame retardant electrode may include an electrode current collector 10, an electrode active material layer 30, and a flame retardant layer 20 disposed between the electrode current collector 10 and the electrode active material layer 30. The flame retardant layer 20 may include a flame retardant having a core-shell structure, a binder, and a first conductive material.

[0041] The electrode current collector 10 may be used as a path for transmitting electrons from the outside so that an electrochemical reaction occurs in the electrode active material in the battery or receiving electrons from the electrode active material and sending them to the outside. When the flame-retardant electrode is used as the negative electrode, the electrode current collector 10 may include a negative electrode current collector, and when the flame-retardant electrode is used as the positive electrode, the electrode current collector 10 may include a positive electrode current collector.

[0042] The electrode active material layer 30 may include an electrode active material that participates in an electrode reaction of a battery including a flame retardant electrode. When the flame retardant electrode is used as a positive electrode, the electrode active material layer 30 may include a positive electrode active material layer, and when the flame retardant electrode is used as a negative electrode, the electrode active material layer 30 may include a negative electrode active material layer.

[0043] The flame retardant layer 20 disposed between the electrode current collector 10 and the electrode active material layer 30 may impart thermal safety by preventing thermal runaway of the flame retardant electrode, and may increase adhesion to the electrode current collector 10 and the electrode active material layer 30 .

[0044] The flame retardant layer 20 may include a layered structure in which a flame retardant, a binder, and a first conductive material are uniformly mixed or dispersed.

[0045] The thickness of the flame retardant layer 20 may be 10 μm or less. When the thickness of the flame retardant layer 20 is 10 μm or less, the thermal stability and adhesion of the electrode may be increased in a balanced manner without deteriorating the electrochemical performance of the battery. If the thickness of the flame retardant layer 20 exceeds 10 μm, the energy density of the battery may decrease. The lower limit of the thickness of the flame retardant layer 20 is not particularly limited. For example, the thickness of the flame retardant layer 20 may be, for example, 100 nm or more, 500 nm or more, or 1 μm or more.

[0046] The binder may be a material that mechanically and physically stabilizes the flame retardant layer 20. The binder may be used as a type of adhesive that bonds the flame retardant and the first conductive material to the electrode current collector 10. Examples of the binder may include, for example, butadiene rubber, nitrile rubber, hydrogenated nitrile rubber, polyvinylidene fluoride (PVDF), polytetrafluoroethylene (PTFE), carboxymethyl cellulose (CMC), and the like.

[0047] The first conductive material can impart electronic conductivity to the flame retardant layer 20. Thus, electrons can move between the electrode current collector 10 and the electrode active material layer 30. The type of the first conductive material is not particularly limited, and can be a material commonly used in batteries, but can be exemplified by a carbon-based conductive material. For example, the carbon-based conductive material can include carbon black, graphite particles, natural graphite, artificial graphite, acetylene black, Ketjen black, carbon nanofibers, carbon nanotubes, or any combination thereof.

[0048] Figure 2 The core-shell structure of the flame retardant according to the embodiment of the present disclosure is exemplified. Figure 2 , the flame retardant may include a core 21 including a flame retardant material and a shell 22 including a second conductive material applied to at least a portion of a surface of the core 21 .

[0049] Generally, flame retardant materials may have lower electronic conductivity than conductive materials. Therefore, when a flame retardant layer including a flame retardant material is located between an electrode current collector and an electrode active material layer, the electronic conductivity of the electrode may be reduced. Since the flame retardant layer according to an embodiment of the present disclosure includes both a flame retardant and a first conductive material, it can suppress the reduction in electronic conductivity caused by the flame retardant. Specifically, by coating the surface of the flame retardant material with a second conductive material, the reduction in electronic conductivity caused by the flame retardant material can be minimized, and a higher electronic conductivity can be obtained than when the flame retardant layer includes only the first conductive material.

[0050] In one embodiment, the flame retardant material may include an endothermic flame retardant material. For example, the flame retardant material may include an inorganic flame retardant material, a phosphorus (P)-based flame retardant material, a halogen-based flame retardant material, a nitrogen (N)-based flame retardant material, or any combination thereof.

[0051] Inorganic flame retardant materials may include aluminum hydroxide (Al(OH) 3 )、Magnesium hydroxide (Mg(OH) 2 ), antimony trioxide (Sb 2 O 3 ), stannous hydroxide (Sn(OH) 2 ), tin oxide (SnO), molybdenum trioxide (MoO 3 ), zirconium compounds, calcium salts, boron compounds or any combination thereof.

[0052] Phosphorus (P)-based flame retardant materials may include red phosphorus (RP)-based flame retardant materials, phosphate-based flame retardant materials, phosphine-based flame retardant materials, phosphite-based flame retardant materials, phosphonate-based flame retardant materials, phosphinate-based flame retardant materials, phosphate-based flame retardant materials, phosphate and phosphate flame retardant materials, or any combination thereof.

[0053] Halogen-based flame retardant materials may include polybrominated diphenyl ethers (PBDE), polybrominated biphenyls (PBB), brominated cyclic hydrocarbons, decabromodiphenyl ether (DeBDE), hexabromocyclododecane (HBCDD), tetrabromobisphenol A (TBBP-A), octabromodiphenyl ether (OBDPE), brominated polystyrene, propylene dibromostyrene, brominated epoxy resins, brominated polycarbonates, chlorinated paraffins, chlorinated polyethylenes, chlorinated alicyclics, or any combination thereof.

[0054] The nitrogen (N)-based flame retardant material may include melamine polyphosphate (MPP), melamine cyanurate, melamine, melamine isocyanurate, a triazine-based compound, or any combination thereof.

[0055] The second conductive material may be applied to the surface of the core 21 to impart improved electronic conductivity to the flame retardant. The type thereof is not particularly limited, and may be a material commonly used in batteries, but may be exemplified by a carbon-based conductive material. For example, the carbon-based conductive material may include carbon black, graphite particles, natural graphite, artificial graphite, acetylene black, Ketjen black, carbon nanofibers, carbon nanotubes, or any combination thereof. Therefore, the second conductive material may be the same as or different from the first conductive material.

[0056] In one embodiment, the thickness w of the shell 22 may be 2 μm or less. The thickness w of the shell 22 may be 1 μm or less. When the thickness w of the shell 22 is 1 μm or less, the flame retardant properties and the electronic conductivity may be improved in a balanced manner without increasing the average particle size of the flame retardant. If the thickness w of the shell 22 exceeds 2 μm, the average particle size of the flame retardant may be excessively increased. In addition, if the thickness w of the shell 22 exceeds 2 μm and the average particle size of the flame retardant can be maintained within a suitable range, the amount of the flame retardant material contained in the flame retardant may be reduced, which results in degraded flame retardant properties. The lower limit of the thickness w of the shell 22 is not particularly limited. For example, the thickness w of the shell 22 may be, for example, 10 nm or more, 50 nm or more, or 100 nm or more.

[0057] In one embodiment, the average particle size of the flame retardant is 50 The thickness of the flame retardant layer 20 including the flame retardant may be 10 μm or less. However, if the average particle size d 50 Exceeding 5 μm may make it difficult to satisfy the thickness range of the flame retardant layer 20. On the other hand, if the average particle size of the flame retardant is less than 3 μm, the amount of the flame retardant material contained in the core 21 may be too small, and the flame retardant property of the flame retardant electrode may be deteriorated.

[0058] In one embodiment, the volume ratio of the core 21 to the sum of the first conductive material and the second conductive material may be 1:1 to 1:100. If the volume of the core is greater than the sum of the volume of the first conductive material and the volume of the second conductive material, the electronic conductivity of the flame-retardant electrode may be reduced, so that the overall electrochemical performance of the battery may be deteriorated. If the volume ratio of the core to the sum of the first conductive material and the second conductive material exceeds 1:100, the energy density of the battery may be reduced due to the excessive amount of the first conductive material and the second conductive material.

[0059] Because the metal lithium film or aluminum film generally used as the electrode current collector may be made of a metal material having a smooth surface, its adhesion to the electrode active material layer may be low. The flame retardant layer 20 according to an embodiment of the present disclosure can enhance the adhesion to the electrode current collector 10 and the electrode active material layer 30 by giving the surface of the electrode current collector 10 a selected, set or predetermined roughness.

[0060] In one embodiment, the adhesion between the flame retardant layer 20 and the electrode current collector 10 may be greater than 0.42 gf / mm. In one embodiment, the adhesion between the flame retardant layer 20 and the electrode current collector 10 may be 1.20 gf / mm or greater. If the adhesion is less than 0.42 gf / mm, it may be difficult to achieve the purpose of obtaining thermal stability and adhesion in a balanced manner. The upper limit of the adhesion is not particularly limited. For example, the adhesion between the flame retardant layer 20 and the electrode current collector 10 may be 10 gf / mm or less.

[0061] In one embodiment, the flame retardant layer 20 may include 0.5 wt% to 5 wt% of a binder. If the amount of the binder included in the flame retardant layer 20 is less than 0.5 wt%, the adhesion of the flame retardant layer 20 to the electrode current collector 10 or the electrode active material layer 30 may be reduced. On the other hand, if the amount of the binder exceeds 5 wt%, the energy density of the battery including the flame retardant electrode may be reduced.

[0062] Furthermore, an all-solid-state battery including the flame-retardant electrode according to an embodiment of the present disclosure may be provided. Figure 3 An all-solid-state battery is exemplarily shown, in which the electrode according to an embodiment of the present disclosure is used as a positive electrode. Figure 3 The all-solid-state battery includes: a positive electrode including a flame-retardant electrode, a solid electrolyte layer 40 located on the positive electrode and including a solid electrolyte, a negative electrode active material layer 50 located on the solid electrolyte layer 40 , and a negative electrode current collector 60 located on the negative electrode active material layer 50 .

[0063] When the flame-retardant electrode is used as a positive electrode, the electrode current collector 10 may be a positive electrode current collector 10 ′, and the electrode active material layer may be a positive electrode active material layer 30 ′.

[0064] The electrode current collector (which is the positive current collector 10') may include a plate-type substrate having conductivity. For example, the positive current collector 10' may include an aluminum foil. The thickness of the positive current collector 10' is not particularly limited, and may be, for example, 1 μm to 500 μm.

[0065] The electrode active material layer (which is the positive electrode active material layer 30') may include a positive electrode active material, a solid electrolyte, a conductive material, a binder, etc. The positive electrode active material is capable of intercalating and deintercalating lithium ions, and examples thereof may include rock-salt-layer-type active materials such as LiCoO 2 、LiMnO 2 、LiNiO 2 , LiVO 2 , Li 1+x Ni 1 / 3 Co 1 / 3 Mn 1 / 3 O 2 etc., spinel-type active materials such as LiMn 2 O 4 、Li(Ni 0.5 Mn 1.5 ) 4 etc., reverse spinel active materials such as LiNiVO 4 , LiCoVO 4 etc.; Olivine-type active materials, such as LiFePO 4 、LiMnPO 4 、LiCoPO 4 、LiNiPO 4 etc.; silicon-containing active materials, such as Li 2 FeSiO 4 , Li 2 MnSiO 4 etc.; rock salt layer type active materials in which part of the transition metal is replaced by a different metal, such as LiNi 0.8 Co (0.2-x) Al x O 2 (0<x<0.2), spinel-type active materials in which a portion of the transition metal is replaced by a different metal, such as Li 1+x Mn 2-x-y M y O 4 (wherein M is at least one selected from Al, Mg, Co, Fe, Ni and Zn, 0<x+y<2), lithium titanate such as Li 4 Ti 5 O 12 wait.

[0066] The solid electrolyte may include an oxide-based solid electrolyte or a sulfide-based solid electrolyte. A sulfide-based solid electrolyte having high lithium ion conductivity may be preferably used. The sulfide-based solid electrolyte is not particularly limited, but examples thereof may include Li 2 SP 2 S 5 , Li 2 SP 2 S 5 -LiI, Li 2 SP 2 S 5 -LiCl, Li 2 SP 2 S 5 -LiBr, Li2 SP 2 S 5 -Li 2 O. Li 2 SP 2 S 5 -Li 2 O-LiI、Li 2 S-SiS 2 , Li 2 S-SiS 2 -LiI, Li 2 S-SiS 2 -LiBr, Li 2 S-SiS 2 -LiCl, Li 2 S-SiS 2 -B 2 S 3 -LiI, Li 2 S-SiS 2 -P 2 S 5 -LiI, Li 2 SB 2 S 3 , Li 2 SP 2 S 5 -Z m S n (wherein m and n are positive numbers, and Z is any one selected from Ge, Zn and Ga), Li 2 S-GeS 2 , Li 2 S-SiS 2 -Li 3 PO 4 , Li 2 S-SiS 2 -Li x MO y (wherein x and y are positive numbers, and M is any one selected from P, Si, Ge, B, Al, Ga, and In), Li 10 G 2 S 12 Examples of oxide-based solid electrolytes may include, for example, perovskite-type LLTO (Li 3x La 2 / 3-x TiO 3 ), phosphate-based NASICON-type LATP (Li 1+x Al x Ti 2-x (PO 4 ) 3 )wait.

[0067] Examples of the conductive material may include carbon black, conductive graphite, ethylene black, graphene, etc. The conductive material included in the positive active material layer 30 ′ may be a separate component from the first and second conductive materials included in the flame retardant layer 20 .

[0068] Examples of the binder may include butadiene rubber, nitrile rubber, hydrogenated nitrile rubber, polyvinylidene fluoride (PVDF), polytetrafluoroethylene (PTFE), carboxymethyl cellulose (CMC), etc. The binder included in the positive active material layer 30' may be a separate component from the binder included in the flame retardant layer 20.

[0069] The solid electrolyte layer 40 may be located between the positive electrode active material layer 30 ′ and the negative electrode active material layer 50 , and may include a solid electrolyte having lithium ion conductivity.

[0070] For example, the solid electrolyte may include an oxide-based solid electrolyte, a sulfide-based solid electrolyte, etc. A sulfide-based solid electrolyte having high lithium ion conductivity may be preferably used.

[0071] The sulfide-based solid electrolyte is not particularly limited, and examples thereof may include Li 2 SP 2 S 5 , Li 2 SP 2 S 5 -LiI, Li 2 SP 2 S 5 -LiCl, Li 2 SP 2 S 5 -LiBr, Li 2 SP 2 S 5 -Li 2 O. Li 2 SP 2 S 5 -Li 2 O-LiI、Li 2 S-SiS 2 , Li 2 S-SiS 2 -LiI, Li 2 S-SiS 2 -LiBr, Li 2 S-SiS 2 -LiCl, Li 2 S-SiS 2 -B2 S 3 -LiI, Li 2 S-SiS 2 -P 2 S 5 -LiI, Li 2 SB 2 S 3 , Li 2 SP 2 S 5 -Z m S n (wherein m and n are positive numbers, and Z is any one selected from Ge, Zn and Ga), Li 2 S-GeS 2 , Li 2 S-SiS 2 -Li 3 PO 4 , Li 2 S-SiS 2 -Li x MO y (wherein x and y are positive numbers, and M is any one selected from P, Si, Ge, B, Al, Ga, and In), Li 10 G 2 S 12 Examples of oxide-based solid electrolytes may include, for example, perovskite-type LLTO (Li 3x La 2 / 3-x TiO 3 ), phosphate-based NASICON-type LATP (Li 1+x Al x Ti 2-x (PO 4 ) 3 ) etc. The solid electrolyte included in the solid electrolyte layer 40 may be the same as or different from the solid electrolyte included in the positive electrode active material layer 30 ′.

[0072] The negative electrode active material layer 50 may include a negative electrode active material, a solid electrolyte, a conductive material, a binder, and the like.

[0073] The negative electrode active material may be a compound capable of reversibly intercalating and deintercalating lithium.

[0074] Specific examples of the negative electrode active material may include carbonaceous materials such as artificial graphite, natural graphite, graphitized carbon fiber, and amorphous carbon; metal compounds capable of alloying with lithium, such as Si, Al, Sn, Pb, Zn, Bi, In, Mg, Ga, Cd, Si alloys, Sn alloys, and Al alloys; metal oxides capable of doping and dedoping lithium, such as SiO β(0<β<2), SnO 2 , vanadium oxide, and lithium vanadium oxide; and a composite material comprising the above metal compound and a carbonaceous material, such as a Si-C or Sn-C composite material, which can be used alone or in combination of two or more thereof.

[0075] Moreover, metallic lithium thin films can be used as negative electrode active materials.

[0076] Since the solid electrolyte, the conductive material, and the binder included in the negative electrode active material layer 50 may be substantially the same as those included in the positive electrode active material layer 30 ′, redundant descriptions thereof will be omitted.

[0077] The negative electrode current collector 60 may include a plate-type substrate having conductivity. For example, the negative electrode current collector 60 may include a material that does not react with lithium. Specifically, the negative electrode current collector 60 may include nickel (Ni), copper (Cu), stainless steel, or any combination thereof. The thickness of the negative electrode current collector 60 is not particularly limited, and may be, for example, 1 μm to 500 μm.

[0078] In addition, an embodiment of the present disclosure relates to an all-solid-state battery, comprising: a negative electrode including a flame-retardant electrode, a solid electrolyte layer located on the negative electrode and including a solid electrolyte, a positive electrode active material layer located on the solid electrolyte layer, and a positive electrode current collector located on the positive electrode active material layer.

[0079] When the electrode current collector is used for the negative electrode, the electrode current collector may be a negative electrode current collector, and the electrode active material layer may be a negative electrode active material layer. Moreover, since the solid electrolyte layer, the positive electrode active material layer and the positive electrode current collector may be substantially the same as those described in the all-solid-state battery to which the positive electrode including the flame-retardant electrode is applied, a detailed description thereof will be omitted.

[0080] A better understanding of the present disclosure can be obtained through the following examples and comparative examples. However, these examples are not to be construed as necessarily limiting the technical spirit of the present disclosure.

[0081] Preparation Example

[0082] (1) Preparation of Sb as flame retardant material in a volume ratio of 1:1 2 O 3 and spherical carbon black as a conductive material. By mixing Sb in a weight ratio of 80:20 2 O 3and some spherical carbon black to obtain a powder in which a flame retardant material and a second conductive material are mixed. The powder is placed in a resonant acoustic mixer and mixed for 30 minutes under a gravitational acceleration of 80G to obtain a flame retardant having a core-shell structure, the flame retardant being configured such that the surface of the core containing the flame retardant material is coated with a shell containing the second conductive material.

[0083] (2) A slurry is prepared by adding a flame retardant, butadiene rubber (BR) as a binder, and spherical carbon black remaining after producing the flame retardant as a first conductive material to butyl butyrate (BB) as an organic solvent, followed by mixing.

[0084] (3) The flame retardant layer 20 is formed on the positive electrode current collector by applying the slurry onto an aluminum thin film as a positive electrode current collector, followed by drying.

[0085] (4) 80 parts by weight of LiNi as the positive electrode active material 0.8 Co 0.1 Mn 0.1 O 2 , 20 parts by weight of Li as a solid electrolyte 6 PS 5 Cl, 2.5 parts by weight of BR as a binder, and 2.5 parts by weight of carbon black as a conductive material were dispersed in BB as an organic solvent to prepare a positive electrode active material slurry. The positive electrode active material slurry was applied to the flame retardant layer and then rolled with a roller press to manufacture a flame retardant positive electrode.

[0086] Comparative Preparation Example 1

[0087] By mixing 80 parts by weight of LiNi as a positive electrode active material 0.8 Co 0.1 Mn 0.1 O 2 , 20 parts by weight of Li as a solid electrolyte 6 PS 5 Cl, 2.5 parts by weight of BR as a binder, and 2.5 parts by weight of carbon black as a conductive material were dispersed in BB as an organic solvent to prepare an active material slurry. The active material slurry was applied to an aluminum thin film and then rolled with a roll press, thereby manufacturing a positive electrode.

[0088] Comparative Preparation Example 2

[0089] (1) Preparation of Sb as flame retardant material with a volume ratio of 2:8 2 O 3 and spherical carbon black as a conductive material.

[0090] (2) By2 O 3 , butadiene rubber (BR) as a binder, and spherical carbon black as a first conductive material are added to butyl butyrate (BB) as an organic solvent, followed by mixing to prepare a slurry.

[0091] Thereafter, a positive electrode was manufactured in the same manner as in Preparation Example.

[0092] Comparative Preparation Example 3

[0093] In addition to preparing Sb as a flame retardant material in a volume ratio of 5:5 2 O 3 A positive electrode was prepared in the same manner as in Comparative Preparation Example 2 except for using spherical carbon black as a conductive material.

[0094] Comparative Preparation Example 4

[0095] In addition to preparing Sb as a flame retardant material in a volume ratio of 6:4 2 O 3 A positive electrode was prepared in the same manner as in Comparative Preparation Example 2 except for using spherical carbon black as a conductive material.

[0096] Comparative Preparation Example 5

[0097] In addition to preparing Sb as a flame retardant material with a volume ratio of 7:3 2 O 3 A positive electrode was prepared in the same manner as in Comparative Preparation Example 2 except for using spherical carbon black as a conductive material.

[0098] Comparative Preparation Example 6

[0099] In addition to preparing Sb as a flame retardant material with a volume ratio of 10:0 2 O 3 A positive electrode was prepared in the same manner as in Comparative Preparation Example 2 except for using spherical carbon black as a conductive material.

[0100] Test Example 1 - Evaluation of Adhesion

[0101] The adhesive force of the positive electrode prepared according to each of the Preparation Example and the Comparative Preparation Example was evaluated. The adhesive force was measured using a tensile strength tester (Daesung Precision Co., Ltd.) in the following manner.

[0102] Each positive electrode is attached to a slide glass using double-sided tape. The width of each positive electrode is cut to match the width of the slide glass, but the length of each positive electrode is fully cut. The part attached to the double-sided tape and the part not attached to the double-sided tape are fixed to each load cell (cell) of a tensile strength tester. The load value depending on displacement is measured by applying tensile stress, and stress values ​​are calculated based on this. Stress values ​​are referred to as bonding force. For example, the results are shown in Table 1 below.

[0103] [Table 1]

[0104] Classification Adhesion force (gf / mm) Preparation Example 1.23 Comparative Preparation Example 1 1.347 Comparative Preparation Example 2 0.935 Comparative Preparation Example 3 1.24 Comparative Preparation Example 4 1.56 Comparative Preparation Example 5 1.235 Comparative Preparation Example 6 0.42

[0105] As shown in Table 1, the adhesion of Comparative Preparation Example 6 in which the flame retardant layer 20 was not formed between the positive current collector 10' and the positive active material layer 30' was measured to be the lowest. Therefore, it is confirmed that the flame retardant layer 20 including the flame retardant, the binder, and the first conductive material enhances the adhesion to the positive current collector 10' and the positive active material layer 30'. This is considered to be because the surface roughness of the positive current collector 10' is improved due to the insertion of the flame retardant layer 20.

[0106] Test Example 2 - Evaluation of Electronic Conductivity

[0107] In order to determine the influence of the flame retardant layer 20 on the electronic conductivity of the positive electrode, the electronic conductivity of the positive electrode according to each of the preparation examples and the comparative preparation examples was measured, and the results are shown in the following Table 2. Therefore, the electronic conductivity of the positive electrode was measured using an electrode electronic conductivity meter (e.g., Biologic, VMP-300).

[0108] [Table 2]

[0109] Classification Electronic conductivity of positive electrode (mS / cm) Preparation Example 1.865 Comparative Preparation Example 1 2.814 Comparative Preparation Example 2 1.784 Comparative Preparation Example 3 0.728 Comparative Preparation Example 4 0.422 Comparative Preparation Example 5 0.055 Comparative Preparation Example 6 0.015

[0110] As shown in Table 2, the electronic conductivity of Comparative Preparation Example 1 not including the flame retardant layer 20 was measured to be the highest. Referring to the results of Comparative Preparation Examples 2 to 6, the electronic conductivity decreases as the amount of the conductive material included in the flame retardant layer 20 decreases.

[0111] When the preparation examples are compared with comparative preparation example 3, the total volume ratio of the flame retardant to the conductive material included in the flame retardant layer 20 is the same, but the electronic conductivity of the preparation example including the flame retardant having a core-shell structure is measured to be higher than that of comparative preparation example 3.

[0112] Example

[0113] According to the preparation example, an electrode assembly is manufactured by stacking a negative electrode current collector 60, a negative electrode active material layer 50, a solid electrolyte layer 40, and a flame retardant positive electrode. A pouch-type all-solid-state battery is obtained by placing the electrode assembly in a case.

[0114] A nickel (Ni) film was used as the negative electrode current collector. The negative electrode was composed of 60 parts by weight of silicon (Si) and natural graphite as negative electrode active materials, 40 parts by weight of Li as a solid electrolyte, and 100 parts by weight of anode material. 6 PS 5 The solid electrolyte layer is composed of 97 parts by weight of Li as a sulfide-based solid electrolyte. 6 PS 5 Cl and 3 parts by weight of BR as a binder.

[0115] Comparative Example 1

[0116] An all-solid-state battery was obtained in the same manner as in Example, except that the positive electrode according to Comparative Preparation Example 1 was used.

[0117] Comparative Example 2

[0118] An all-solid-state battery was obtained in the same manner as in Example, except that the positive electrode according to Comparative Preparation Example 2 was used.

[0119] Comparative Example 3

[0120] An all-solid-state battery was obtained in the same manner as in Example except that the positive electrode according to Comparative Preparation Example 3 was used.

[0121] Comparative Example 4

[0122] An all-solid-state battery was obtained in the same manner as in Example except that the positive electrode according to Comparative Preparation Example 4 was used.

[0123] Comparative Example 5

[0124] An all-solid-state battery was obtained in the same manner as in Example, except that the positive electrode according to Comparative Preparation Example 5 was used.

[0125] Comparative Example 6

[0126] An all-solid-state battery was obtained in the same manner as in Example, except that the positive electrode according to Comparative Preparation Example 6 was used.

[0127] Test Example 3 - Evaluation of Thermal Stability Using ARC

[0128] Figure 4A photograph of an accelerating calorimeter (ARC) for measuring the thermal stability of the all-solid-state battery according to the embodiment and comparative example 1 is shown. The all-solid-state battery according to each of the embodiments and comparative examples was charged at 4.25V SOC 100%, and then heated in an insulating state to measure the temperature change of the battery. Here, series 1 to 5 were measured to confirm the area where thermal runaway occurs in the all-solid-state battery. When the battery self-heating reaction is measured, the temperature increase is stopped and the heating temperature of the battery is measured. The specific ARC evaluation conditions are shown in Table 3 below.

[0129] [Table 3]

[0130] Starting temperature Final temperature Sensitivity Add Steps Increased stabilization time 50℃ 250℃ 0.02℃ / min 5℃ 50 minutes

[0131] Figure 5 Results of analyzing an all-solid-state battery according to an embodiment using an accelerating rate calorimeter are shown. Figure 6 The results of analyzing the all-solid-state battery according to Comparative Example 1 using an accelerating calorimeter are shown. Here, T 1 is the self-heating starting temperature of the all-solid-state battery, and T 2 is the thermal runaway temperature. In addition, T 2 The front and rear flat parts were set as heating parts. The results are shown in Table 4 below.

[0132] [Table 4]

[0133] <![CDATA[T 1 ]]> <![CDATA[T 2 ]]> Heating unit Example 174.87℃ 213.46℃ short Comparative Example 1 166.78℃ 328.7℃ long

[0134] refer to Figure 5 , it was observed that the results of the accelerated calorimeter analysis of series 1 to series 5 of Example 1 were very similar and difficult to distinguish from each other. In this case, a peak was observed at about 2900 minutes. The peak temperatures of series 2 to 5 were similar to each other, and the thermal runaway temperature (T 2 ).

[0135] according to Figure 6 , it was observed that the accelerated calorimeter analysis results of Series 1 to Series 5 of Comparative Example 1 were very similar and difficult to distinguish from each other. In this case, a peak was observed around 3500 minutes, and the peak temperatures of Series 1 to 4 were similar to each other, and a clear thermal runaway temperature (T 2 ).

[0136] like Figure 5 and Figure 6As shown in Table 4, when the flame retardant layer 20 including a flame retardant having a core-shell structure is applied to the positive electrode, the self-heating start temperature of the all-solid-state battery including it increases and the maximum temperature during thermal runaway decreases. In addition, the heating portion before and after the thermal runaway time point is shortened. Therefore, compared with Comparative Example 1, it is confirmed that the thermal stability of the all-solid-state battery according to the embodiment is improved.

[0137] Test Example 4 - Evaluation of Thermal Stability Using DSC

[0138] In order to determine the amount of heat generated in the all-solid-state batteries according to the examples and the comparative examples, the all-solid-state batteries were analyzed using differential scanning calorimetry (DSC), and the results are shown in FIG. Figure 7 and Table 5 below.

[0139] [Table 5]

[0140] Classification Starting temperature (℃) Heat generated (J / g) Example 205.75 438.0 Comparative Example 1 176 930.5 Comparative Example 2 172 861.49 Comparative Example 3 202 453.4 Comparative Example 4 203 428.52 Comparative Example 5 219 246.11 Comparative Example 6 212 219.56

[0141] As shown in Table 5, the amount of generated heat decreases as the amount of the flame retardant included in the flame retardant layer 20 increases. In addition, the onset temperature generally increases as the amount of the flame retardant increases.

[0142] Test Example 5-Evaluation of the electrochemical characteristics of all-solid-state batteries

[0143] The charge / discharge test was conducted on the embodiment, comparative example 1 and comparative example 3. The discharge end voltage and the charge end voltage were set to 2.0 V and 4.25 V, respectively, and the rate was set to 0.2C. The results are shown in Figure 8 middle.

[0144] Reference Figure 8 , the discharge capacity of the all-solid-state battery according to the embodiment was measured to be approximately 193 mAh / g, the discharge capacity of the all-solid-state battery according to Comparative Example 1 was measured to be approximately 197 mAh / g, and the discharge capacity of the all-solid-state battery according to Comparative Example 3 was measured to be approximately 185 mAh / g.

[0145] Therefore, compared with Comparative Example 3 using a flame retardant without a second conductive material, it was confirmed that the embodiment using a flame retardant having a core-shell structure exhibited excellent discharge capacity. Moreover, it was found that the discharge capacity of the embodiment was similar to that of Comparative Example 1 not including the flame retardant layer 20.

[0146] As apparent from the above description, the electrode according to the embodiment of the present disclosure includes a flame retardant layer disposed between an electrode current collector and an electrode active material layer, and the flame retardant layer includes all of a flame retardant, a binder, and a conductive material, so that thermal stability and adhesion can be increased.

[0147] In particular, the flame retardant may have a core-shell structure in which a flame retardant material serves as a core and a conductive material serves as a shell, thereby increasing thermal stability and adhesion and also ensuring electrochemical performance similar to that of an all-solid-state battery that does not include a flame retardant layer.

[0148] The embodiments and advantages of the present disclosure are not necessarily limited to the above-mentioned embodiments and advantages. It can be understood that the embodiments of the present disclosure can include all effects and advantages that can be inferred from the description of the present disclosure.

Claims

1. A flame retardant electrode, comprising: Electrode current collector; Electrode active material layer; as well as a flame retardant layer, the flame retardant layer being located between the electrode current collector and the electrode active material layer, The flame retardant layer comprises a flame retardant having a core-shell structure, an adhesive and a first conductive material, and The flame retardant includes a core including a flame retardant material and a shell including a second conductive material applied to at least a portion of a surface of the core.

2. The flame-retardant electrode according to claim 1, wherein: The flame retardant layer has a thickness of 10 μm or less.

3. The flame-retardant electrode according to claim 1, wherein: The shell has a thickness of 2 μm or less.

4. The flame-retardant electrode according to claim 1, wherein: The flame retardant has an average particle size of 3 μm to 5 μm.

5. The flame-retardant electrode according to claim 1, wherein: A volume ratio of the core to the sum of the first conductive material and the second conductive material is 1:1 to 1:

100.

6. The flame retardant electrode according to claim 1, wherein: The flame retardant material includes at least one material selected from the group consisting of an inorganic flame retardant material, a phosphorus-based flame retardant material, a halogen-based flame retardant material, and a nitrogen-based flame retardant material.

7. The flame-retardant electrode according to claim 1, wherein: The flame retardant material includes at least one inorganic flame retardant selected from the group consisting of Al(OH)3, Mg(OH)2, Sb2O3, Sn(OH)2, SnO, MoO3, zirconium compounds, calcium salts and boron compounds.

8. The flame-retardant electrode according to claim 1, wherein: The flame retardant material includes at least one phosphorus-based flame retardant material selected from the group consisting of: red phosphorus-based flame retardant materials, phosphate-based flame retardant materials, phosphine-based flame retardant materials, phosphite-based flame retardant materials, phosphonate-based flame retardant materials, phosphinate-based flame retardant materials, phosphate-based flame retardant materials, and phosphate-and-phosphate flame retardant materials.

9. The flame-retardant electrode according to claim 1, wherein: The flame retardant material includes at least one halogen-based flame retardant material selected from the group consisting of polybrominated diphenyl ethers, polybrominated biphenyls, brominated cyclic hydrocarbons, decabromodiphenyl ether, hexabromocyclododecane, tetrabromobisphenol A, octabromodiphenyl ether, brominated polystyrene, propylene dibromostyrene, brominated epoxy resins, brominated polycarbonates, chlorinated paraffins, chlorinated polyethylenes, and chlorinated alicyclics.

10. The flame retardant electrode according to claim 1, wherein: The flame retardant material includes at least one nitrogen-based flame retardant material selected from the group consisting of melamine polyphosphate, melamine cyanurate, melamine, melamine isocyanurate, and a triazine-based compound.

11. The flame-retardant electrode according to claim 1, wherein: The flame retardant layer has an adhesive force with the electrode current collector of 1.20 gf / mm or more.

12. The flame-retardant electrode according to claim 1, wherein: The flame retardant layer includes 0.5 wt % to 5 wt % of the binder.

13. The flame retardant electrode according to claim 1, wherein: The first conductive material and the second conductive material include a carbon-based conductive material.

14. An all-solid-state battery, comprising: Positive electrode current collector; positive electrode active material layer; as well as a flame retardant layer located between the positive electrode current collector and the positive electrode active material layer, wherein the flame retardant layer comprises a flame retardant having a core-shell structure, a binder, and a first conductive material, and wherein the flame retardant comprises a core comprising a flame retardant material and a shell comprising a second conductive material applied to at least a portion of a surface of the core, wherein the positive electrode current collector, the positive electrode active material layer, and the flame retardant layer form a positive electrode; a solid electrolyte layer, the solid electrolyte layer being located on the positive electrode and comprising a solid electrolyte; a negative electrode active material layer, the negative electrode active material layer being located on the solid electrolyte layer; and A negative electrode current collector is located on the negative electrode active material layer.

15. The all-solid-state battery according to claim 14, wherein: The thickness of the flame retardant layer is 10 μm or less, the thickness of the shell is 2 μm or less, and the average particle size of the flame retardant is 3 μm to 5 μm.

16. The all-solid-state battery according to claim 14, wherein: The flame retardant material includes at least one material selected from the group consisting of an inorganic flame retardant material, a phosphorus-based flame retardant material, a halogen-based flame retardant material, and a nitrogen-based flame retardant material.

17. An all-solid-state battery, comprising: Anode current collector; A negative electrode active material layer; as well as a flame retardant layer, the flame retardant layer being located between the negative electrode current collector and the negative electrode active material layer, wherein the flame retardant layer comprises a flame retardant having a core-shell structure, a binder and a first conductive material, and wherein the flame retardant comprises a core comprising a flame retardant material and a shell comprising a second conductive material applied to at least a portion of a surface of the core, wherein the negative electrode current collector, the negative electrode active material layer and the flame retardant layer form a negative electrode; a solid electrolyte layer, the solid electrolyte layer being located on the negative electrode and comprising a solid electrolyte; a positive electrode active material layer, the positive electrode active material layer being located on the solid electrolyte layer; and A positive electrode current collector is located on the positive electrode active material layer.

18. The all-solid-state battery according to claim 17, wherein: The thickness of the flame retardant layer is 10 μm or less, the thickness of the shell is 2 μm or less, and the average particle size of the flame retardant is 3 μm to 5 μm.

19. The all-solid-state battery according to claim 17, wherein: The flame retardant material includes at least one material selected from the group consisting of an inorganic flame retardant material, a phosphorus-based flame retardant material, a halogen-based flame retardant material, and a nitrogen-based flame retardant material.